PENGARUH DAYA TARIK WISATA, ELECTRONIC WORD OF MOUTH, DAN CITRA DESTINASI WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE DESA WISATA LUBUK KERTANG, KABUPATEN LANGKAT - Prayogi, Budi; Dalimunthe, Femmy Indriani; Tondang, Bahagia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Lubuk Kertang Tourism Village is a tourist destination in North Sumatra whose existence is not quite popular compared to other tourist villages in North Sumatra which are in the Toba Caldera Region. For this reason, in-depth analysis is needed in various aspects to increase tourist visits to this village. This research is a quantitative descriptive research that aims to determine the effect of tourist attraction, electronic word of mouth, and the image of a tourist destination on the decision to visit tourists to Lubuk Kertang Tourism Village, Langkat Regency. The sample of this research is 100 people taken by using accidental sampling method. Data related to the 4 tested variants were obtained through questionnaires and analyzed using multiple linear regression analysis. The results of the study show that there is a partial and simultaneous influence of tourist attraction, electronic word of mouth, and the image of a tourist destination on the decision to visit tourists to Lubuk Kertang Tourism Village. Thus improving the quality of these three variables is needed so that tourist visits to Lubuk Kertang can increase.